Keragaman dan Kepadatan Populasi Predator yang Berasosiasi dengan Hama Penting pada Tanaman Kubis (Brassica oleracea L.) - NI WAYAN ASRIANI; I GUSTI NGURAH BAGUS; NI NENGAH DARMIATI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2013)
ABSTRACT The Predator Diversity and Population Density Associated with Important Pest in Cabbage Plant (Brassica Oleracea L.) The cabbage plant (Brassica oleracea var. capitata L.) is an important vegetable especially in the highland, has been much cultivated and tried by farmers in Indonesia especially in rural areas. The vitamins contained in cabbage that is vitamin A, B and C which have important role in fulfilling human needs. The aim of this research is to find out the diversity and density of predator population associated with important pests in cabbage plant. To find out about the progress of predator population density associated with important pests in cabbage plant. The result of observation to the diversity of predator’s types showed that five types of predators were found associated with important pests in cabbage plant that was Menochilus sexmaculatus, Ischiodon scutellaris, Paederus fuscipes Curt, Dolichoderus bituberculatus, Oecophylla smaragdina. Diversity index of these types of predators was classified as low which was (0.60). Key words: Predator and Cabbage plant.